2019
DOI: 10.1155/2019/2965872
|View full text |Cite
|
Sign up to set email alerts
|

Noncontact Meibography in Patients with Keratoconus

Abstract: Purpose. To examine the morphological changes in the meibomian glands of patients with keratoconus as well as to study the relationship between these changes in the morphology and several tear film parameters. Methods. Examination of the meibomian gland (MG) of 300 keratoconus patients presenting to the center using infrared noncontact meibography system (Sirius, CSO, Italy) between January 2017—January 2019. 100 eyes of healthy individuals were also enrolled as a control group. Tear breakup time (TBUT) test a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 32 publications
(34 reference statements)
1
19
0
Order By: Relevance
“…Keratoconus is a multifactorial disease with genetic, environmental, in ammatory, hormonal risk factors and eye rubbing playing role in etiopathogenesis [17]. In the literature, few studies reported on increased dry eye symptoms [7,18], tear lm instability [6,19], ocular surface staining [6, 7] and conjunctival metaplasia with goblet cell loss in keratoconus patients [5][6][7]. indicating involvement of whole ocular surface epithelium and tear lm in the disease process in these eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Keratoconus is a multifactorial disease with genetic, environmental, in ammatory, hormonal risk factors and eye rubbing playing role in etiopathogenesis [17]. In the literature, few studies reported on increased dry eye symptoms [7,18], tear lm instability [6,19], ocular surface staining [6, 7] and conjunctival metaplasia with goblet cell loss in keratoconus patients [5][6][7]. indicating involvement of whole ocular surface epithelium and tear lm in the disease process in these eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that subjects with irregular corneas are more likely to suffer from DED and MGD [42][43][44]. Moreover, McMonnies [61] and Lema et al [62] also suggested that a possible inflammatory role might be involved in the pathogenesis of keratoconus since inflammatory molecules were overexpressed in the tears of subjects with keratoconus.…”
Section: Effect Of Scleral Lens Wear In Ocular Surface Symptoms Gland Drop-out and Gland Visibilitymentioning
confidence: 99%
“…The sample of this study represented irregular corneas, except for four of them. Since scleral lenses are usually fitted in subjects with irregular corneas, who are more likely to suffer from DED [42][43][44], assessing the effect of these lenses on meibomian glands is vital. Thus, a recent review confirmed that there is a need for prospective evaluation of meibomian gland appearance and function during scleral lens wear [11].…”
Section: Effect Of Scleral Lens Wear In Ocular Surface Symptoms Gland Drop-out and Gland Visibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…11–13 Evaluating dry eye parameters in KC patients revealed low tear break-up time (TBUT) and marked corneal staining, increased the Ocular Surface Disease Index© (OSDI) scores, dropout, and distortion in MGs. 8,14–16…”
mentioning
confidence: 99%